At the source of Vilnius Altaic studies - Tulisow, Jerzy (Acta Orientalia Vilnensia, 2009)
University of Warsaw This paper presents the life and achievements of three Polish Orientalists connected with Vilnius: Mongolist Józef Kowalewski (1801–1878), Turkologist Antoni Muchliński (1808–1877), and Altaist and Mongolist Władysław Kotwicz (1872–1944).